Active learning: effective teaching strategies / Najah Mokhtar... [et al.] - Mokhtar, Najah; Andin Salamat, Azni Syafena; Abd Rahim, Maisarah (2010)
Students are the main assets of learning institutions. The performance of students should be the main concern of educators in creating students with excellence performance. The role of an educator is to facilitate the students’ learning process. The educator has to create a conducive and attractive learning environment to ensure the teaching is effective in order to stimulate students’ interest. Through traditional teaching methods, students passively receive information from the lecturers. Therefore, it is important to know the practice of active learning that significantly improve performance for students in classes with substantial use of interactive-engagement methods. The core elements of active learning are student activity and engagement in the learning process. It involves the students to solve problems, answer questions, formulate questions of their own, discuss, explain, debate, or brainstorm during class. A review of the past and current literature indicates that active learning has significant contribution towards students’ performance. Active learning strategies have proven in more retention of subject matter and a deeper comprehension of the concepts covered in class. This paper presents the practices of active learning in the classroom to facilitate student’s learning and reflection.